A Short Review of Online Learning Assessment Strategies - Adan Amer; Gaganpreet Sidhu; Zhao Bo; Seshasai Srinivasan (International Journal of Pedagogy and Teacher Education, 2022)
The COVID-19 pandemic has caused a paradigm shift in how teachers, instructors and students approach teaching and learning, especially concerning the migration to online learning environments. One of the most challenging aspects of adapting to online/virtual education is evaluating students’ knowledge acquisition through learning assessments. The lack of face-to-face proctoring renders many of the traditional paper-based assessment techniques impractical, especially in the context of an engineering education that is heavily focused on applied learning. Since virtual education now represents an important evolution in education, it is pertinent for educators to familiarise themselves with the new possibilities of assessment methods in a virtual setting and to design tailored assessment strategies for individual courses. This article reviews and summarises commonly employed virtual assessment methods that are applicable to most engineering educational situations, such as open-book exams, online quizzes, or peer assessments. The paper also discusses some concerns that may arise in implementing these methods. Additionally, there is a particular focus on qualitatively-graded ePortfolios as a unique pedagogical tool in the virtual classroom due to their role as both a repository for storing learning artifacts and a vehicle for advancing students’ learning experience.